Gonaphodioides zempoaltepetlensis (Coleoptera: Scarabaeidae: Aphodiinae), a new species from Oaxaca, Mexico - Dellacasa, Marco; Dellacasa, Giovanni; Arriaga-Jiménez, Alfonsina (Zootaxa, 2018)
The genus Gonaphodioides Dellacasa, Dellacasa, & Gordon, 2012 (Coleoptera: Scarabaeidae: Aphodiinae: Aphodiini) was created for seven species distributed in Mesoamerica and South America. Subsequently, G. cartwrighti Dellacasa, Dellacasa, & Gordon, 2013 was described from El Salvador (Dellacasa et al. 2013).